High rate of positive lymph nodes in T1a gallbladder cancer does not translate to decreased survival: a population-based, propensity score adjusted analysis. Issue 11 (November 2018) - Köhn, Nastassja; Maubach, Johannes; Warschkow, Rene; Tsai, Catherine; Nussbaum, Daniel P.; Candinas, Daniel; Gloor, Beat; Schmied, Bruno M.; Blazer, Dan G.; Worni, Mathias
Abstract: Background: Current consensus guidelines suggest that gallbladder cancer (GBC) patients with resected T1a disease can be observed while patients with T1b or greater lesions should undergo lymphadenectomy (LNE). The primary aim of this study was to critically explore the impact of LNE in early-stage GBC on overall survival (OS) on a population-based level. Method: The 2004–2014 National Cancer Database was reviewed to identify non-metastatic GBC patients with T1a, T1b, or T2 disease and grouped whether a dedicated LNE was performed. OS and relative survival were assessed using Cox proportional hazard regression analyses before and after propensity score adjustments. Results: 4015 patients were included, 246 (6%) had T1a, 654 (16%) T1b, and 3115 (78%) T2 GBC. The rate of positive lymph nodes was 13%, 12%, and 40% for T1a, T1b, and T2 tumors, respectively. Even after propensity score adjustment, no OS benefit was found if LNE was performed for T1a disease (HR:0.63, 95%CI:0.35–1.13) while OS was improved for T1b (HR:0.65, 95%CI:0.49–0.87) and T2 tumors (HR:0.65, 95%CI:0.57–0.73). Conclusion: Despite a higher rate of nodal positivity among patients with T1a disease compared to previous reports, there was no impact on survival and current treatment guidelines appear appropriate for the management of T1a disease.